Pengaruh Literasi Wakaf dan Altruisme terhadap Minat Generasi Milenial Berwakaf Uang di Kota Banda Aceh Dimoderasi Religiusitas - Siti Alfia Nur Auliana; Eka Nurlina; Khairil Umuri; Ridwan Nurdin; Muftahuddin Muftahuddin (Badan Wakaf Indonesia, 2026)
This research aims to analyze the influence of waqf literacy and altruism on the interest of the millennial generation in giving cash waqf in Banda Aceh City with religiosity as a moderating variable. The sample used in the research consisted of 100 respondents selected using nonprobability sampling techniques. The data analysis techniques used are multiple linear regression analysis and moderate regression analysis. The results of the research show that waqf literacy has a positive and significant effect on the interest of the millennial generation in cash waqf in Banda Aceh City. Altruism has a negative but significant effect on the interest of the millennial generation in waqf in Banda Aceh City. The religiosity variable cannot moderate the relationship between waqf literacy and the interest of the millennial generation in waqf in Banda Aceh City